Switch - Law, Ingrid 1970- (New York, New York : Dial Books for Young Readers, an imprint of Penguin Group (USA) LLC, 2015)
"Gypsy Beaumont's magical savvy switches to its opposite when she learns that her mean and decidedly non-magical grandma has Alzheimer's and is going to move in with her family"--
Keywords: Magic -- Juvenile fiction; Families -- Juvenile fiction; Grandmothers -- Juvenile fiction; Alzheimer's disease -- Juvenile fiction; Magic -- Fiction; Families -- Fiction; Grandmothers -- Fiction; Alzheimer's disease -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / Family / Multigenerational